VD_FINDINFO HC / 2012 / 542 vom 8. August 2012 - VD Tribunal cantonal (2012)
FRAIS JUDICIAIRES, ACTION EN MODIFICATION, JUGEMENT DE DIVORCE | 284 al. 3 CPC (CH), 291 CPC (CH), 95 al. 1 CPC (CH), 54 TFJC (2010)